165 The Metabolomic Profile of Umbilical Cord Blood in Neonatal Hypoxic Ischaemic Encephalopathy. (October 2012) - Walsh, BH; Broadhurst, D; Mandal, R; Wishart, DS; Boylan, GB; Kenny, LC; Murray, DM
Abstract : Background: Hypoxic ischaemic encephalopathy (HIE) is associated with the activation of multiple biochemical pathways. The importance of these pathways individually, and that of their interaction, in the disease process is not fully understood. The aim of this study was to describe and quantify the metabolomic profile of umbilical cord blood samples in a carefully defined population of full-term infants with HIE. Methods: Full-term infants with perinatal asphyxia (with and without HIE) and healthy controls had umbilical cord blood drawn and bio-banked at –80°C, within 3 hours of birth. A combined direct injection and LC-MS/MS assay (AbsolutIDQ p180 kit, Biocrates Life Sciences AG, Innsbruck, Austria) was used for the metabolomic analyses of the samples. The degree of encephalopathy among those with asphyxia was defined using both continuous multichannel-EEG in the first 24 hours, and modified Sarnat score. Results: 142 neonates were included in the analysis (HIE=31, asphyxia without encephalopathy=40, controls=71). There was a significant alteration (p<0.01) in 29 metabolites from 3 distinct metabolite classes (Amino Acids, Carnitines, and Phosphatidylcholines) between study groups. 13 of these metabolites were significantly altered between HIE and controls. Cross-validated Partial Least Square Discriminant Analysis models were developed to distinguish between the groups. The HIE model differentiated significantly between HIE, and those without HIE (AUC=0.93, R 2 = 0.36, Q 2 = 0.25). Conclusion: The description of the metabolomic profile from umbilical cord plasma and the specific metabolite signature associated with HIE, offers insight into the disease mechanism and the possibility of an early screening test.